Ti3C2Tx MXene Nanosheets as a Robust and Conductive Tight on Si Anodes Significantly Enhance Electrochemical Lithium Storage Performance - Xia, Mengting; Chen, Bingjie; Gu, Feng; Zu, Lianhai; Xu, Mengzhu; Feng, Yutong; Wang, Zhijun; Zhang, Haijiao; Zhang, Chi; Yang, Jinhu (ACS nano, 2020)
Exploring Si-based anode materials with high electrical conductivity and electrode stability is crucial for high-performance lithium-ion batteries (LIBs). Herein, we propose the fabrication of a Si-based composite where Si porous nanospheres (Si p-NSs) are tightly wrapped by Ti3C2Tx (Tx stands for the surface groups such as -OH, -F) MXene nanosheets (TNSs) through an interfacial assembly strategy. The TNSs as a conductive and robust tight of the Si p-NSs can effectively improve electron transport and electrode stability, as revealed by substantial characterizations and mechanical simulations. Moreover, the TNSs with rich surface groups enable strong interfacial interactions with the Si p-NS component and a pseudocapacitive behavior, beneficial for fast and stable lithium storage. Consequently, the Si p-NS@TNSs electrode with a high Si content of 85.6% exhibits significantly enhanced battery performance compared with the Si p-NSs electrode such as high reversible capacity (1154 mAh g-1 at 0.2 A g-1), long cycling stability (up to 2000 cycles with a 0.026% capacity decay rate per cycle), and excellent rate performances. Notably, the Si p-NS@TNSs electrode-based LIB full cell delivers a high energy uptake of 405 Wh kg-1, many-times higher than that of the Si p-NSs full cell. This work offers a strategy to develop advanced Si-based anode materials with desirable properties for high-performance LIBs.Exploring Si-based anode materials with high electrical conductivity and electrode stability is crucial for high-performance lithium-ion batteries (LIBs). Herein, we propose the fabrication of a Si-based composite where Si porous nanospheres (Si p-NSs) are tightly wrapped by Ti3C2Tx (Tx stands for the surface groups such as -OH, -F) MXene nanosheets (TNSs) through an interfacial assembly strategy. The TNSs as a conductive and robust tight of the Si p-NSs can effectively improve electron transport and electrode stability, as revealed by substantial characterizations and mechanical simulations. Moreover, the TNSs with rich surface groups enable strong interfacial interactions with the Si p-NS component and a pseudocapacitive behavior, beneficial for fast and stable lithium storage. Consequently, the Si p-NS@TNSs electrode with a high Si content of 85.6% exhibits significantly enhanced battery performance compared with the Si p-NSs electrode such as high reversible capacity (1154 mAh g-1 at 0.2 A g-1), long cycling stability (up to 2000 cycles with a 0.026% capacity decay rate per cycle), and excellent rate performances. Notably, the Si p-NS@TNSs electrode-based LIB full cell delivers a high energy uptake of 405 Wh kg-1, many-times higher than that of the Si p-NSs full cell. This work offers a strategy to develop advanced Si-based anode materials with desirable properties for high-performance LIBs.